Testing the Quantity-Quality Fertility Model: The Use of Twins as a Natural Experiment - Rosenzweig, Mark R.; Wolpin, Kenneth I. (Econometrica, 1980)
The predictive content of the quantity-quality model of fertility and the empirical information required for verification under a minimal set of restrictions on the utility function is described. It is demonstrated that commodity-independent compensated price effects must be known to infer the existence of the unobservable interdependent shadow prices of the model with a relatively weak structure improsed on preference orderings. A method of using multiple birth events to substitute for these exogenous prices is proposed and applied to household data from India.